Analysis of Patient Registration Satisfaction Using Self-Registration Machine with End User Computing Satisfaction (EUCS) Method - Hasinuddin, M; Kurniawati, Rizka; Zainiyah, Zakkiyatus; Haris, Mustofa; Kulsum, Ummi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Health Service Facilities are places to organize health service efforts, both promotive, preventive, curative and rehabilitative. Health services that are the first service in the health level of a region are Hospitals. One of the technologies that is currently developing is the Self-Registration Queue Machine (APM). This innovation project report aims to identify the level of satisfaction with the use of the Self-Registration Queue Machine for patients or the Community at Anna Medika Hospital Madura. This innovation project report was conducted on patients/families who use APM machines at Anna Medika Hospital, Madura. The sampling technique in this study used the Incidental Sampling Technique so that the respondents in this study were 18 respondents. The type of research used in this study is descriptive quantitative with a cross-sectional approach. The questionnaire research instrument was declared valid and reliable. The data analysis used was descriptive and univariate analysis. The results of the study showed the percentage of group calculations from the Format dimension 0.566 (56.6%) and Ease of Use 0.544 (59.5%) included in the moderate category, the Content dimension 0.722 (72.2%), Accurancy 0.811 (81.1%) and Timelines 0.656 (65.6%) were in the good category. This indicates that the satisfaction of APM machine users is running well and needs to be maintained, so there needs to be socialization for officers who are less supportive. The purpose of using APM machines is to reduce registration time at the counter for health services provided to improve services for outpatient needs.